Understanding the church involvement of generation Z adults within megachurches in Indonesia - Pranoto, Irwan (Ann Arbor, MI : ProQuest Dissertation, 2021)
The purpose of this descriptive qualitative study was to understand and describe Gen Z adults’ church involvement within Chinese-background megachurches in Indonesia. This study used basic qualitative research to achieve its purpose to construct meaning from the participants. All 24 participants were living in Indonesia. They consisted of 9 participants who are church leaders, over the age of 25; and 15 other participants who represented Gen Z and were within the age range of 18-to-25-year-olds. The author conducted one-on-one interviews with each participant that lasted from 60 to 90 minutes. The interviews were recorded, transcribed, translated, and analyzed using standard coding procedures, which involved the initial and focused coding. The author also conducted participant observations on the church online worship services and some church activities that involved Gen Z, such as small group meetings and gatherings. The study’s findings describe how the churches’ strategies and endeavors in ministering to today’s young people had led Gen Z to have characteristic church involvement practices, challenges, and impacts on their lives and others around them. Additionally, this study’s findings also spell out the three prominent factors in churches that led to Gen Z’s church involvement, including an engaging community, empowering responsibility, and elevating spirituality. These findings add to the theoretical understanding of Gen Z’s characteristics within the Indonesian context, factors contributing to church involvement, and Chinese-background megachurches in Indonesia. Moreover, this study’s findings also indicate practical implications primarily for the Chinese-background megachurches in Indonesia, the young people ministries of today’s churches, and the researchers in ministry to the young people in Indonesia.
Memahami Keterlibatan Gerejawi Generasi Z Usia Dewasa Dalam Gereja-Gereja Besar (Megachurches) Di Indonesia
Ph.D--Biola University, 2021
Keywords: Church work with youth; Church work with students.; Youth -- Religious life.; Gen Z; church involement; megachurches; Chinese-background megachurches in Indonesia; young people ministry; college students